Experimental tests on SHS aluminium beams under non-uniform bending. (15th September 2022) - Nastri, Elide; Piluso, Vincenzo; Pisapia, Alessandro
Highlights: 12 experimental tests on box-shaped aluminium beams under non-uniform bending. The material properties, failure modes, moment resistance, end rotation capacity and strain response of specimens have been reported. Evaluation of local buckling effects on the ultimate resistance of aluminium beams. Comparison between the experimental results with those obtained by means of current Eurocode provisions. Evaluation of accuracy of the new approaches provided in the Annex L of the revised Eurocode 9. Abstract: The results of an experimental program dealing with SHS (Square Hollow Section) aluminium beams subjected to non-uniform bending are presented and discussed. Three-point bending tests have been performed on extruded SHS aluminium beams, made of 6060 alloy temper T66, with different width-to-thickness ratios. The material mechanical properties, the maximum flexural resistance, the rotation capability and the failure mode are reported in the manuscript. A finite element model is calibrated and validated against the force versus displacement experimental curves. Both the experimental and numerical results are compared with the current European design provisions, given in EN 1999-1-1. In particular, the different approaches suggested by EN 1999-1-1 are compared with the tests' results. The results obtained have shown that the ultimate resistance predicted by the codified provisions given in the general part of EN 1999-1-1 is, generally, on the safe side. Moreover, the refined effective thickness method (ETM) suggested in Annex L of revised EN 1999-1-1 is also applied. The refined method has shown higher accuracy in estimating the ultimate flexural resistance.